Factors predicting health practitioners' awareness of UNHS program in Malaysian non-public hospitals - Ismail, Abdussalaam Iyanda; Abdul Majid, Abdul Halim; Zakaria, Mohd Normani; Abdullah, Nor Azimah Chew; Hamzah, Sulaiman; Mukari, Siti Zamratol-Mai Sarah (Elsevier B.V, 2018)
Objective :The current study aims to examine the effects of human resource (measured with the perception of health workers' perception towards UNHS), screening equipment, program layout and screening techniques on healthcare practitioners' awareness (measured with knowledge) of universal newborn hearing screening (UNHS) in Malaysian non-public hospitals. Methods: Via cross sectional approach, the current study collected data using a validated questionnaire to obtain information on the awareness of UNHS program among the health practitioners and to test the formulated hypotheses. 51, representing 81% response rate, out of 63 questionnaires distributed to the health professionals were returned and usable for statistical analysis. The survey instruments involving healthcare practitioners' awareness, human resource, program layout, screening instrument, and screening techniques instruments were adapted and scaled with 7-point Likert scale ranging from 1 (little) to 7 (many). Partial Least Squares (PLS) algorithm and bootstrapping techniques were employed to test the hypotheses of the study.Results With the result involving beta values, t-values and p-values (i.e. β=0.478, t=1.904, p<0.10; β=0.809, t=3.921, p<0.01; β= -0.436, t=1.870, p<0.10), human resource, measured with training, functional equipment and program layout, are held to be significant predictors of enhanced knowledge of health practitioners. Likewise, program layout, human resource, screening technique and screening instrument explain 71% variance in health practitioners' awareness. Health practitioners' awareness is explained by program layout, human resource, and screening instrument with effect size (f2) of 0.065, 0.621, and 0.211 respectively, indicating that program layout, human resource, and screening instrument have small, large and medium effect size on health practitioners' awareness respectively. However, screening technique has zero effect on health practitioners' awareness, indicating the reason why T-statistics is not significant.Conclusion: Having started the UNHS program in 2003, non-public hospitals have more experienced and well-trained employees dealing with the screening tools and instrument, and the program layout is well structured in the hospitals. Yet, the issue of homogeneity exists. Non-public hospitals charge for the service they render, and, in turn, they would ensure quality service, given that they are profit-driven and/or profit-making establishments, and that they would have no option other than provision of value-added and innovative services. The employees in the non-public hospitals have less screening to carry out, given the low number of babies delivered in the private hospitals. In addition, non-significant relationship between screening techniques and healthcare practitioners' awareness of UNHS program is connected with the fact that the techniques that are practiced among public and non-public hospital are similar and standardized. Limitations and suggestions were discussed.